Models and Strategies for Digital SMEs Development in Ambon City - Salomi J. Hehanussa; Mozes D Istia (International Journal of Scientific Multidisciplinary Research, 2023)
The research entitled "Digital SMEs Development Models And Strategies In Ambon City" is an interesting thing to research, relating to the important role of SMEs in the Indonesian economy. This is proven by various research results which say that SMEs are a type of business that can withstand the shocks of the economic crisis. On the other hand, the Ministry of Industry launched a strategy for making SMEs in the era of technology 4.0 to empower SMEs that are competitive at local, national and international levels. The quarterly rate of economic development reached 2.06 percent (q-to-q), while y-on-y grew 5.73 percent and annually or cumulatively reached 15.11 percent (c-on-c). Based on the 2016 Economic Census, the number of SMEs in Maluku Province was 147,000 or 99.15%, with labor absorption of 0.35 million people or 87.75%. (BPS: Economic Census, 2016). This shows that SMEs have a strategic role in absorbing labor. In line with this, the development of digital SMEs is important for adopting communication and information technology innovations in the business world, in order to increase competitiveness and manage resources efficiently. The reality of the role of SMEs in the business world by adopting technological innovation needs to be explored in this research, so the objectives of this research are as follows: (1) Building an ideal model for using digital technology in the 4.0 era for SMEs in Ambon City